Cariogenic Foods as the Cause of Dental Caries in Children - Daud, Serly; Said, Hariadi (Universitas Sam Ratulangi, 2022)
Abstract: Issue of dental carries which is closely related to the consumption of cariogenic food, has not only become a dental health [roblem, but has also become an avid research interest in the room of scholarly research discussion. This study aimed to present an illustration of the association between cariogenic food and the occurence of dental caries in children. This was a literature review study using a descriptive research design. The electronic data base Science Technology Index (SINTA), specifically SINTA 2 and SINTA 3, was used to collect the appropriate reviewed articles, by using the entry keywords of â€œkariesâ€ â€œcariesâ€, â€œkaries gigi pada anakâ€, â€œdental caries in childrenâ€, â€œmakanan kariogenikâ€, and â€œcariogenic foodsâ€. The results obtained seven articles fitting the topics. All articles stated that consumption of cariogenic foods including sweet food, carbohydrate-rich food, and sweet drink played an important role in the occurrence of dental caries among children. In conclusion, cariogenic food contributing to dental caries issue in children included sweet and carbohydrate foods as well as soft drinks.Keywords: dental caries; cariogenic food; childrenÂ Abstrak: Isu karies gigi yang lekat kaitannya dengan konsumsi makanan kariogenik tidak hanya menjadi masalah di bidang kesehatan gigi, tetapi juga telah menjadi bahan riset menarik dalam ruang diskusi kajian ilmiah. Penelitian ini bertujuan untuk menggambarkan hubungan antara makanan kariogenik dengan kejadian karies gigi pada anak. Jenis penelitian ialah suatu literature review dengan desain penelitian deskriptif. Penelusuran bahan pustaka dilakukan dengan cara memasukkan kata kunci â€œkariesâ€ â€œcariesâ€, â€œkaries gigi pada anakâ€, â€œdental caries in childrenâ€, â€œmakanan kariogenikâ€, dan â€œcariogenic foodsâ€ dengan memanfaatkan basis data Science Technology Index (SINTA), khususnya SINTA 2 dan SINTA 3. Hasil penelitian mendapatkan tujuh artikel yang sesuai dengan topik bahasan. Ketujuh artikel tersebut manyatakan bahwa mengonsumsi makan kariogenik yang mencakup makanan manis, berkarbohidrat maupun minuman ringan manis berandil besar tehadap kejadian karies gigi pada anak. Simpulan penelitian ini ialah makanan kariogenik yang menjadi biang masalah terjadinya karies gigi pada anak meliputi makanan manis dan berkarbohidrat serta minuman ringan.Kata kunci: karies gigi; makanan kariogenik; anak